Vehicle brake disc and preparation process thereof
By using TiC and B4C ceramic particles reinforced aluminum-based composite materials in vehicle brake discs, combined with arc additive manufacturing and split design processes, the existing brake discs have been solved in material and structure, achieving the goals of high performance and low cost.
Patent Information
- Application Number
- CN202510018058.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
AI Technical Summary
Existing vehicle brake discs have shortcomings in materials, structure, performance and manufacturing processes, and it is difficult to meet the market demands of lightweight, low cost and high performance.
The functional structural layer is prepared through arc additive manufacturing technology, combining pressure casting and mechanical processing technology, breaking the traditional integrated structure and using split design and combined manufacturing.
The brake disc functional structure has achieved good inner toughness and strong wear resistance, and the overall high-temperature mechanical properties and shock absorption. It has reduced production costs and manufacturing processes, and improved the life and reliability of the brake disc.
Smart Images

Figure CN119825850A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of vehicle brake discs, and in particular to a vehicle brake disc and a preparation process thereof. Background Art
[0002] With the development of new energy vehicles and special vehicles, new requirements have been put forward for the lightweight and performance of vehicle brake discs (brake discs). At present, commercial vehicle brake discs are still mostly cast in gray cast iron or alloy materials, which are heavy and cannot meet the needs of energy saving and consumption reduction. Although the publicly disclosed new lightweight material vehicle brake discs, such as aluminum-based composite materials, titanium-based composite materials, carbon / carbon composite materials and other vehicle brake discs, meet the lightweight requirements, they are difficult to replace the market position of traditional cast iron and alloy vehicle brake discs due to many reasons such as high manufacturing cost, short service life and complex process flow. The development of low-cost, new structure, lightweight vehicle brake discs that meet market demand is of great significance to social progress and industry development.
[0003] The Chinese invention patent publication number is CN107760894A, the publication date is 2018.03.06, and the name of the invention is "A method for preparing an aluminum-based composite automobile brake disc". A silicon carbide ceramic reinforced aluminum-based composite automobile brake disc is developed by the method of integral melting + machining + heat treatment. Although the invention has good lightweight and high wear resistance, the silicon carbide with a volume fraction of up to 20-45% causes great damage to the tool and mold, and the processing cost is high. In addition, the invention does not consider the limitations of the mechanical properties of silicon carbide particles reinforced aluminum-based composite materials. The mechanical properties of the mounting surface of the one-piece cast ceramic / aluminum composite vehicle brake disc are difficult to meet the requirements of vehicle equipment.
[0004] The Chinese invention patent publication number is CN106812837A, the publication date is 2017.06.09, and the invention is named "an aluminum-based composite brake disc and preparation method". It uses a split casting method to first cast the aluminum disc core, and then cast the ceramic particle reinforced aluminum-based composite material on the surface of the disc core as a friction layer. Although the brake disc solves the brittleness problem of the one-piece composite disc core, the split casting process is complicated, and it is difficult to ensure the bonding strength of the two casting joints.
[0005] The Chinese invention patent publication number is CN111074109A, the publication date is 2020.04.28, and the name of the invention is "Dual-phase ceramic particle reinforced aluminum-based composite material and brake drum and preparation method thereof". SiC and TiB2 dual-phase ceramic particles are used as reinforcement phases, and aluminum-based composite brake drums are prepared by pressure casting process. The core content of this invention is the in-situ synthesis of a SiC and TiB2 dual-phase ceramic particle reinforced aluminum-based composite material, and the dual-phase ceramic particles are randomly distributed, which does not fundamentally solve the structural and processing problems of the one-piece cast ceramic / aluminum composite brake drum (disc).
[0006] Based on the defects of current automobile brake discs, it is necessary to improve them. Summary of the invention
[0007] In view of the deficiencies of existing vehicle brake discs in terms of materials, structure, performance and manufacturing process, the present invention provides a vehicle brake disc and a preparation process thereof to solve the respective shortcomings of the existing integral composite brake disc and mechanical combination brake disc, simplify the process flow, and optimize the structure and performance of a new lightweight aluminum-based vehicle brake disc.
[0008] The present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a vehicle brake disc, comprising:
[0010] Disc base;
[0011] Functional structural layers are respectively embedded on two surfaces of the disc base;
[0012] Wherein, one end surface of each of the functional structural layers is embedded in the disc base, and the other end surface is flush with the surface of the disc base;
[0013] The functional structural layer includes a matrix, TiC ceramic particles, and B4C ceramic particles;
[0014] Wherein, the volume fraction of the TiC ceramic particles increases with the increase of the thickness of the functional structure layer from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer;
[0015] When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of the thickness of the functional structure layer, the volume fraction of the TiC ceramic particles decreases as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles increases as the thickness of the functional structure layer increases.
[0016] Preferably, the volume fraction of the TiC ceramic particles increases from 0% to 20-30% as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles is 0% from the end surface embedded in the disc base to the 1 / 2-5 / 8 position of the thickness of the functional structure layer;
[0017] When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of the thickness of the functional structure layer, the volume fraction of the TiC ceramic particles decreases from 20 to 30% to 3 to 5% as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles increases from 0% to 10 to 20% as the thickness of the functional structure layer increases.
[0018] Preferably, the functional structure layer extends from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer, and the functional structure layer includes a plurality of first sub-functional structure layers stacked in layers, and the volume fraction of B4C ceramic particles in each first sub-functional structure layer is 0%; wherein the volume fraction of TiC ceramic particles in the first sub-functional structure layer farthest from the surface of the disc base is 0%, and the volume fraction difference of TiC ceramic particles in any two adjacent first sub-functional structure layers is 3 to 5%;
[0019] The thickness of the functional structure layer is from 1 / 2 to 5 / 8 of the thickness of the functional structure layer to the end face flush with the surface of the disc base, and the functional structure layer includes a plurality of stacked second sub-functional structure layers; wherein the volume fraction of TiC ceramic particles in the second sub-functional structure layer farthest from the surface of the disc base is 15 to 25%, the volume fraction of B4C ceramic particles is 3 to 4%, the volume fraction difference of TiC ceramic particles in any two adjacent second sub-functional structure layers is 4 to 6%, and the volume fraction difference of B4C ceramic particles is 2 to 4%.
[0020] Preferably, the particle size of the TiC ceramic particles is 25 to 60 μm; the particle size of the B4C ceramic particles is 45 to 300 μm.
[0021] Preferably, the disc base comprises:
[0022] A disc body having a central hole;
[0023] A connecting portion, which is located in the central hole of the disc body, and is provided with a connecting hole;
[0024] The functional structural layers are respectively embedded on two surfaces of the disc body;
[0025] One end surface of each functional structure layer is embedded in the disc body, and the other end surface is flush with the surface of the disc body.
[0026] Preferably, the cross-sectional shape of the functional structural layer is any one of a circular ring shape, an involute shape, an elliptical ring shape, and a diamond sheet shape.
[0027] Preferably, the end surface of the functional structure layer that is flush with the surface of the disc base is also provided with a capping layer;
[0028] The material of the disc base includes any one of Al-Si alloy and Al-Mg alloy;
[0029] The material of the substrate is Al-Mg alloy;
[0030] The material of the capping layer is Al-Mg alloy;
[0031] The thickness of the functional structure layer is 30-35% of the thickness of the disc base;
[0032] The distance between the end surface of the cover layer away from the disc base and the surface of the disc base is less than or equal to 1 mm.
[0033] In a second aspect, the present invention further provides a process for preparing the vehicle brake disc, comprising the following steps:
[0034] preparing a disc base;
[0035] Grooves are respectively machined on two surfaces of the disc base, and the grooves are adapted to the functional structure layer;
[0036] Determining an additive manufacturing deposition path according to the structure of the functional structural layer;
[0037] TiC ceramic particles and B4C ceramic particles are placed in two powder feeders with independent powder feeding channels respectively, and the two powder feeding channels are connected to a wire-powder synchronous deposition composite welding gun head;
[0038] Install the alloy welding wire corresponding to the substrate on the wire feeder;
[0039] According to the additive manufacturing deposition path, arc additive deposition is carried out and the powder feeding rate of TiC ceramic particles and B4C ceramic particles is controlled to print the functional structure layer in the groove.
[0040] Preferably, the process parameters controlled during arc additive deposition are: deposition current of 90-110A, fuse speed of 5.0-6.0m / min, arc swing amplitude of 4-10mm, arc swing frequency of 2-5Hz, capture rate of TiC ceramic particles by the molten pool of 60-70%, and capture rate of B4C ceramic particles by the molten pool of 30-40%.
[0041] Preferably, the disc base is prepared by a pressure casting process;
[0042] After the functional structure layer is prepared, a cap layer is prepared on the surface of the functional structure layer, and then the cap layer is ground so that the distance between the end surface of the cap layer and the surface of the disc base is less than or equal to 1 mm;
[0043] During arc additive deposition, the width of a single deposition layer is 5 to 20 mm, and the thickness of each layer is 0.5 to 2 mm.
[0044] The vehicle brake disc and the manufacturing process thereof of the present invention have the following beneficial effects compared with the prior art:
[0045] 1. The innovation of the vehicle brake disc of the present invention lies in coupling the advantages of TiC and B4C ceramic particles reinforced aluminum-based composite materials, performing dual-gradient optimization on the distribution of TiC and B4C ceramic particles, achieving the performance advantages of good toughness of the inner layer of the functional structure of the brake disc, strong wear resistance of the outer layer, and excellent overall high-temperature mechanical properties and shock absorption; the dual-phase ceramic particle gradient-enhanced vehicle brake disc of the present invention has a non-continuous distribution of functional structures on its friction braking surface, which is beneficial to the release of friction stress and friction heat diffusion between the functional structure and the disc base during braking, thereby improving the service life of the brake disc and increasing the reliability of vehicle braking; compared with traditional vehicle brake discs, the brake disc with a functional structure configuration has a higher artistic added value, and the configuration can also be customized according to customer requirements to meet personalized market needs;
[0046] 2. The vehicle brake disc of the present invention has a disc base and a lower part of a functional structure layer with a higher strength than a conventional gray cast iron (HT250) brake disc, and a functional structure layer with a strength equivalent to that of gray cast iron. The thermal conductivity is more than three times that of gray cast iron, the shock absorption (damping) is better than that of gray cast iron, the friction coefficient and braking capacity are equivalent to those of gray cast iron, and the wear resistance is far superior to that of gray cast iron;
[0047] 3. The preparation process of the vehicle brake disc of the present invention is innovative in that it breaks the one-piece structure of the traditional vehicle brake disc and adopts split design and combined manufacturing, which not only solves the problem of difficult processing and low mechanical properties of the one-piece composite brake disc, but also avoids the problem of complicated assembly process of the mechanical combined brake disc. First, the aluminum alloy disc base embryo of the vehicle brake disc of the present invention is produced by traditional pressure casting, which simplifies the process, reduces the cost, and ensures the mechanical properties of the brake disc base; secondly, the mechanical milling of the vehicle brake disc of the present invention is only for the aluminum alloy disc base embryo, and there is no problem of difficult processing of the integral composite brake disc; in addition, the vehicle brake disc of the present invention is only manufactured for the friction braking surface for composite material functional structure, that is, local enhancement, avoiding the weakening of the mechanical properties of the non-braking part of the brake disc by the integral composite material; further, the composite material functional structure is manufactured by the arc additive process of silk-powder synchronous deposition, which not only has a simple process flow, but also can ensure the metallurgical bonding of the functional structure and the aluminum alloy disc base, while reducing the abuse of reinforcement materials and scientifically exerting the energy efficiency advantages of a combination of multiple materials;
[0048] 4. The preparation process of the vehicle brake disc of the present invention adopts a combined process of pressure casting + machining + additive manufacturing + grinding finishing, which organically integrates the comprehensive advantages of multiple processes, avoids the high-energy consumption overall heat treatment process, further reduces the production cost, shortens the manufacturing process, and is easy to automate and mass-produce;
[0049] 5. The preparation process of the vehicle brake disc of the present invention, the selected aluminum-based materials and ceramic reinforcements have good thermal conductivity, and will not generate sparks under high-speed braking, and can be applied to some special production fields, such as special vehicles in the fields of mining, smelting, and energy transportation. The aluminum-based vehicle brake disc with dual-phase ceramic particle gradient reinforcement of the present invention can be repaired by the arc additive manufacturing process of silk-powder synchronous deposition after the friction surface and functional structure are worn, which can greatly extend the service life of the vehicle brake disc and further reduce the product cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0051] Figure 1 It is a schematic structural diagram of the functional structural layer of the present invention;
[0052] Figure 2 It is a schematic diagram of the structure of the functional structure layer and the cover layer of the present invention being superimposed;
[0053] Figure 3 A schematic structural diagram of a solid vehicle brake disc having a multi-segment annular functional structural layer according to the present invention;
[0054] Figure 4 A side view of a solid vehicle brake disc having a multi-segment annular functional structural layer according to the present invention;
[0055] Figure 5 A schematic structural diagram of a solid vehicle brake disc having an involute-shaped functional structural layer according to the present invention;
[0056] Figure 6 A side view of a solid vehicle brake disc having an involute-shaped functional structural layer according to the present invention;
[0057] Figure 7 A schematic structural diagram of a solid vehicle brake disc having an elliptical ring-shaped functional structural layer according to the present invention;
[0058] Figure 8 A side view of a solid vehicle brake disc having an elliptical ring-shaped functional structural layer according to the present invention;
[0059] Fig. 9 A schematic structural diagram of a solid vehicle brake disc having a diamond-shaped functional structural layer according to the present invention;
[0060] Fig.10 A side view of a solid vehicle brake disc having a diamond-shaped functional structural layer according to the present invention;
[0061] Fig.11 This is the variation pattern of the volume fraction of TiC ceramic particles and the volume fraction of B4C ceramic particles in each functional structure layer in Example 1. DETAILED DESCRIPTION
[0062] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] In the description of the present invention, it should be understood that the directions or positions indicated by “upper” and the like are based on the directions or positions shown in the accompanying drawings, or are the directions or positions in which the product of the invention is usually placed when in use, or are directions or positions commonly understood by those skilled in the art. These directions or positions are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or component referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present invention.
[0064] Furthermore, the terms “first”, “second”, etc. are merely used for distinguishing descriptions and should not be understood as indicating or implying relative importance.
[0065] The order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0066] The present application embodiment provides a vehicle brake disc, such as Figures 1 to 10 As shown, including:
[0067] Disc base 1;
[0068] The functional structure layer 2 is respectively embedded on two surfaces of the disc base 1;
[0069] Among them, one end surface of each functional structure layer 2 is embedded in the disc base 1, and the other end surface is flush with the surface of the disc base 1.
[0070] The functional structural layer includes a matrix, TiC ceramic particles, and B4C ceramic particles;
[0071] Among them, the volume fraction of TiC ceramic particles increases with the increase of the thickness of the functional structure layer 2 from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer;
[0072] When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of the thickness of the functional structure layer, the volume fraction of TiC ceramic particles decreases with the increase of the thickness of the functional structure layer, and the volume fraction of B4C ceramic particles increases with the increase of the thickness of the functional structure layer.
[0073] The vehicle brake disc of the present invention comprises a disc base 1 and a functional structure layer 2, wherein the functional structure layer 2 is respectively embedded in two surfaces of the disc base 1; the functional structure layer 2 comprises a matrix, TiC ceramic particles, and B4C ceramic particles; the functional structure layer 2 is embedded in the disc base from the end surface to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer, specifically, refer to Figure 1 As shown, Figure 1 A to B is the distance from the end face of the functional structure layer 2 embedded in the disc base to the 1 / 2 to 5 / 8 position of the thickness of the functional structure layer. In the direction from A to B, the volume fraction of TiC ceramic particles increases with the increase of the thickness of the functional structure layer. When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of the thickness of the functional structure layer, that is, from the 1 / 2 to 5 / 8 position of the thickness of the functional structure layer to the end face flush with the surface of the disc base 1, that is, Figure 1 From B to C, the volume fraction of TiC ceramic particles decreases with the increase of the thickness of the functional structure layer; that is, at the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer 2, the volume fraction of TiC ceramic particles reaches the maximum value; when the thickness of the functional structure layer 2 is from 1 / 2 to 5 / 8 of the thickness of the functional structure layer to the end surface flush with the surface of the disc base 1, the volume fraction of B4C ceramic particles increases with the increase of the thickness of the functional structure layer; refer again Figure 1 As shown in the figure, B to C are the thickness of the functional structure layer 2, and from the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer to the end face flush with the surface of the disc base 1, in the direction from B to C, the volume fraction of TiC ceramic particles decreases with the increase of the thickness of the functional structure layer, and the volume fraction of B4C ceramic particles increases with the increase of the thickness of the functional structure layer; the dual-phase ceramic particle gradient reinforced vehicle brake disc of the present invention is innovative in that it couples the advantages of TiC and B4C ceramic particle reinforced aluminum-based composite materials, and performs dual distribution of TiC and B4C ceramic particles. Gradient optimization realizes the performance advantages of good toughness of the inner layer of the functional structure of the brake disc, strong wear resistance of the outer layer, and excellent overall high-temperature mechanical properties and shock absorption. The dual-phase ceramic particle gradient-enhanced vehicle brake disc of the present invention has a non-continuous distribution of functional structures on its friction braking surface, which is beneficial to the release of friction stress and friction heat diffusion between the functional structure and the disc base during braking, thereby improving the life of the brake disc and increasing the reliability of vehicle braking. Compared with traditional vehicle brake discs, brake discs with functional structure configurations have higher artistic added value, and the configuration can also be customized according to customer requirements to meet personalized market needs.
[0074] In some embodiments, the functional structure layer 2 is from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer. At this time, the functional structure layer 2 includes a matrix and TiC ceramic particles. The volume fraction of the TiC ceramic particles increases from 0% to 20-30% as the thickness of the functional structure layer increases. The volume fraction of the B4C ceramic particles is 0%, and the rest is the matrix.
[0075] When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of the thickness of the functional structure layer, specifically, when the thickness of the functional structure layer 2 is from 1 / 2 to 5 / 8 of the thickness of the functional structure layer to the end face flush with the surface of the disc base 1, at this time, the functional structure layer 2 includes a matrix, TiC ceramic particles, and B4C ceramic particles. The volume fraction of the TiC ceramic particles decreases from 20 to 30% to 3 to 5% as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles increases from 0% to 10 to 20% as the thickness of the functional structure layer increases, and the rest is the matrix.
[0076] In some embodiments, reference Figure 2 As shown, the functional structure layer 2 is from the end face embedded in the disc base to the position where the thickness of the functional structure layer is 1 / 2 to 5 / 8, and the functional structure layer 2 includes a plurality of first sub-functional structure layers 21 stacked together, wherein the volume fraction of TiC ceramic particles in the first sub-functional structure layer 21 farthest from the surface of the disc base is 0%, and the difference in volume fraction of TiC ceramic particles in any two adjacent first sub-functional structure layers is 3 to 5%, and the volume fraction of TiC ceramic particles in the first sub-functional structure layer 21 closest to the surface of the disc base is 20 to 30%, and the difference in volume fraction of TiC ceramic particles in any two adjacent first sub-functional structure layers 21 is 3 to 5%.
[0077] In some embodiments, reference Figure 2 As shown, from the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer 2 to the end face flush with the surface of the disc base 1, the functional structure layer 2 includes a plurality of stacked second sub-functional structure layers 22; wherein, the volume fraction of TiC ceramic particles in the second sub-functional structure layer farthest from the surface of the disc base 22 is 15-25%, and the volume fraction of B4C ceramic particles is 3-4%, and the volume fraction of TiC ceramic particles in the second sub-functional structure layer closest to the surface of the disc base 22 is 3-5%, and the volume fraction of B4C ceramic particles is 10-20%; the volume fraction difference of TiC ceramic particles in any two adjacent second sub-functional structure layers 22 is 4-6%, and the volume fraction difference of B4C ceramic particles is 2-4%.
[0078] In the above embodiment, the functional structural layer 2 includes a matrix and TiC ceramic particles. The volume fraction of the TiC ceramic particles is calculated as follows: the volume of the TiC ceramic particles is obtained by dividing the mass of the TiC ceramic particles by their density. The volume of the melted and deposited Al-Mg alloy welding wire is the volume of the matrix. The volume of the TiC ceramic particles is divided by the sum of the volumes of the TiC ceramic particles and the matrix to obtain the volume fraction of the TiC ceramic particles.
[0079] In the above embodiment, the functional structural layer 2 includes a matrix, TiC ceramic particles, and B4C ceramic particles. The volume fraction of the TiC ceramic particles is calculated as follows: the volume of the TiC ceramic particles is obtained by dividing the mass of the TiC ceramic particles by their density. The volume of the melted and deposited Al-Mg alloy welding wire is the volume of the matrix. The volume of the B4C ceramic particles is obtained by dividing the mass of the B4C ceramic particles by their density. The volume of the TiC ceramic particles is divided by the sum of the volumes of the TiC ceramic particles, the B4C ceramic particles, and the matrix to obtain the volume fraction of the TiC ceramic particles. The volume fraction of the B4C ceramic particles is calculated as follows: the volume of the B4C ceramic particles is divided by the sum of the volumes of the TiC ceramic particles, the B4C ceramic particles, and the matrix to obtain the volume fraction of the B4C ceramic particles.
[0080] In some embodiments, the particle size of the TiC ceramic particles is 25-60 μm; the particle size of the B4C ceramic particles is 45-300 μm.
[0081] In some embodiments, the disc base 1 comprises:
[0082] A disc body 11 having a central hole 10;
[0083] A connecting portion 12 is located in the central hole 10 of the disc body 11, and a connecting hole 13 is provided on the connecting portion 12;
[0084] The functional structure layer 2 is respectively embedded on two surfaces of the disc body 11;
[0085] One end surface of each functional structural layer 2 is embedded in the disc body 11 , and the other end surface is flush with the surface of the disc body 11 .
[0086] In some embodiments, the cross-sectional shape of the functional structural layer 2 is any one of a circular ring shape, an involute shape, an elliptical ring shape, and a diamond sheet shape;
[0087] The circumferential surface of the disc body 11 is also provided with a plurality of ventilation holes 14, which are connected with the central hole 10; if there are ventilation holes, the brake disc is a ventilated disc; if there are no ventilation holes, the brake disc is a solid disc.
[0088] For further reference, Figures 3-4 As shown, the disc base 1 includes a disc body 11, and the cross-sectional shape of the functional structure layer 2 is annular, specifically, three concentric circular rings staggered inside and outside; the width of the circular ring segment is 15mm, the spacing is 30mm, the difference in radius between the inner and outer circular rings is 25mm, and the thickness of the functional structure layer is 8mm.
[0089] refer to Figures 5-6As shown, the disc base 1 includes a disc body 11, and the cross-sectional shape of the functional structure layer 2 is an involute shape, the width of the functional structure line is 25 mm, the start and end ends are 10 mm away from the inner and outer edges of the brake disc braking surface, and the thickness of the functional structure layer is 10 mm.
[0090] refer to Figures 7-8 As shown, the disc base 1 includes a disc body 11, and the cross-sectional shape of the functional structure layer 2 is an elliptical ring, and there are two elliptical ring-shaped functional structure layers 2 of different sizes that are staggered inside and outside. The major axis of the large elliptical ring-shaped functional structure layer 2 is 36mm, the minor axis is 15mm, and the ring width is 12mm. The major axis of the small elliptical ring-shaped functional structure layer is 16mm, the minor axis is 10mm, the ring width is 6mm, and the thickness of the functional structure layer is 8mm.
[0091] refer to Figures 9-10 As shown, the disc base 1 includes a disc body 11, and the cross-sectional shape of the functional structure layer 2 is a diamond-shaped sheet, and there are two diamond-shaped functional structure layers 2 of different sizes that are staggered inside and outside. The side length of the large diamond-shaped functional structure layer 2 is 40mm, and the obtuse angle is 125°, and the length of the small diamond-shaped functional structure layer 2 is 35mm, and the obtuse angle is 100°; the thickness of the functional structure layer is 10mm.
[0092] In some embodiments, reference Figure 2 As shown, the end surface of the functional structure layer 2 which is flush with the surface of the disc base 1 is also provided with a cover layer 3.
[0093] In some embodiments, the material of the disc base includes any one of Al-Si and Al-Mg alloys such as ZL101, ZL102, A356, A357, ZL301, and ZL303.
[0094] In some embodiments, the material of the substrate is an Al-Mg alloy.
[0095] In some embodiments, the material of the cap layer is Al-Mg alloy.
[0096] In some embodiments, the thickness of the functional structural layer is 30-35% of the thickness of the disc base;
[0097] In some embodiments, the thickness of the disc base is 25-45 mm; the thickness of the functional structure layer is 8-15 mm.
[0098] In some embodiments, the distance between the end surface of the cover layer away from the disc base and the surface of the disc base is less than or equal to 1 mm. Preferably, the thickness of the cover layer is 0.5-1 mm.
[0099] Based on the same inventive concept, the present invention also provides a process for preparing the above-mentioned vehicle brake disc, comprising the following steps:
[0100] S1, preparing a disc base;
[0101] S2, processing grooves on two surfaces of the disc base respectively, wherein the grooves are adapted to the functional structure layer;
[0102] S3. Determine an additive manufacturing deposition path according to the structure of the functional structural layer;
[0103] S4, placing TiC ceramic particles and B4C ceramic particles in two powder feeders with independent powder feeding channels respectively, and the two powder feeding channels are connected to a wire-powder synchronous deposition composite welding gun head;
[0104] S5. Install the alloy welding wire corresponding to the substrate on the wire feeder;
[0105] S6. According to the additive manufacturing deposition path, arc additive deposition is performed and the powder feeding rate of TiC ceramic particles and B4C ceramic particles is controlled to print in the groove to obtain a functional structural layer.
[0106] In some embodiments, the process parameters controlled during arc additive deposition are: deposition current of 90 to 110 A, fuse speed of 5.0 to 6.0 m / min, arc swing amplitude of 4 to 10 mm, arc swing frequency of 2 to 5 Hz, capture rate of TiC ceramic particles by the molten pool of 60 to 70%, and capture rate of B4C ceramic particles by the molten pool of 30 to 40%.
[0107] In some embodiments, the disc base is prepared by a pressure casting process;
[0108] After the functional structure layer is prepared, a cover layer is prepared on the surface of the functional structure layer, and then the cover layer is ground so that the distance between the end surface of the cover layer and the braking area surface of the disc base is less than or equal to 1 mm;
[0109] During arc additive deposition, the width of a single deposition layer is 5 to 20 mm, and the thickness of each layer is 0.5 to 2 mm.
[0110] In the above embodiment, the silk-powder synchronous deposition composite welding gun head is an existing conventional silk-powder synchronous deposition composite welding gun head.
[0111] In some embodiments, a process for preparing a vehicle brake disc comprises: producing an aluminum alloy disc base blank by a pressure casting process; then, machining the surface of the disc base blank, and milling grooves corresponding to the functional structure layer on both sides thereof, and processing a brake disc connecting hole; then, sequentially preparing a functional structure layer and a cover layer in the grooves corresponding to the surface of the brake disc by an arc additive manufacturing process using silk-powder synchronous deposition, and the surface of the cover layer protrudes from the surface of the disc base by about 1 to 2 mm; finally, grinding and finishing the functional structure surface according to the design size requirements, and the processed functional structure surface is about 0.5 to 1 mm higher than the surface of the disc base.
[0112] In some embodiments, the present invention uses an arc additive manufacturing process that can achieve wire-powder synchronous deposition to prepare a dual-phase ceramic particle gradient reinforced aluminum-based composite functional structure. This method integrates arc fuse deposition and multi-channel powder injection process, which is not only low-cost, but also can flexibly configure the required different contents and types of materials at the specified position of the brake disc. The process is as follows:
[0113] S1. Fix the disc base with the groove processed on the positioner with adjustable speed, and clean the area to be prepared;
[0114] S2, drying TiC ceramic particles and B4C ceramic particles and placing them in two powder feeders with independent powder feeding channels respectively, and the two powder feeding channels are connected to the wire-powder synchronous deposition composite welding gun head;
[0115] S3, use a robot or CNC machine tool to control the welding gun, and cooperate with the positioner to run in the corresponding groove according to the trajectory of functional structure layered slicing. The width of a single deposition layer is 5 to 20 mm. The number of deposition passes for each layer is determined according to the functional structure slicing area, and the thickness of each layer is 0.5 to 2 mm;
[0116] S4, using the swing arc process to promote the metallurgical bonding between the deposited layer and the disc base, the first layer of Al-Mg alloy is deposited as the base layer;
[0117] S5. Starting from the second layer, the TiC powder feeding channel is started, and the TiC powder feeding rate is increased layer by layer to ensure that the volume fraction of TiC reaches the designed peak content when the deposition layer reaches 1 / 2 to 5 / 8 of the thickness of the functional structure. At the same time, the B4C powder feeding channel is started, and the B4C powder feeding rate is increased and the TiC powder feeding rate is reduced layer by layer to ensure that the volume fraction of B4C reaches the designed peak content when the deposition layer and the surface of the disc base are basically flat.
[0118] S6. Finally, a 1 to 2 mm thick Al-Mg alloy is deposited on the surface of each functional structure as a cover layer, which is used as a subsequent grinding finishing allowance; the vehicle brake disc with the prepared functional structure is finished by a grinding process, and the cover layer is ground to no higher than 1 mm from the surface of the disc base.
[0119] The preparation process of the vehicle brake disc of the present invention is innovative in that it breaks the integrated structure of the traditional vehicle brake disc, adopts split design and combined manufacturing, which not only solves the problem of difficult processing and low mechanical properties of the integrated composite brake disc, but also avoids the problem of complex assembly process of the mechanical combined brake disc. First, the aluminum alloy disc base embryo of the vehicle brake disc of the present invention is produced by traditional pressure casting, which simplifies the process, reduces the cost, and ensures the mechanical properties of the brake disc base; secondly, the mechanical milling of the vehicle brake disc of the present invention is only for the aluminum alloy disc base embryo, and there is no problem of difficult processing of the integral composite brake disc; in addition, the vehicle brake disc of the present invention is only for the friction braking surface. Composite material functional structure manufacturing, that is, local enhancement, avoids the weakening of the mechanical properties of the non-braking part of the brake disc by the integral composite material; further, the composite material functional structure is manufactured by the arc additive process of wire-powder synchronous deposition, which not only has a simple process flow, but also can ensure the metallurgical bonding of the functional structure and the aluminum alloy disc base, while reducing the abuse of reinforcement materials, and scientifically exerting the energy efficiency advantages of multiple material combinations. Another innovation of the dual-phase ceramic particle gradient-reinforced aluminum-based vehicle brake disc of the present invention is that it couples the advantages of two ceramic particle-reinforced aluminum-based composite materials, TiC and B4C, and performs dual-gradient optimization on the distribution of the two ceramic particles of TiC and B4C, thereby achieving the performance advantages of the functional structure of the brake disc having good inner toughness, strong outer wear resistance, and excellent overall high-temperature mechanical properties and shock absorption. The dual-phase ceramic particle gradient-reinforced aluminum-based vehicle brake disc of the present invention is manufactured using a combined process of pressure casting + machining + additive manufacturing, organically integrating the comprehensive advantages of multiple processes, avoiding the overall heat treatment process with high energy consumption, further reducing production costs, shortening the manufacturing process, and facilitating automation and large-scale production. The dual-phase ceramic particle gradient-reinforced aluminum-based vehicle brake disc of the present invention has good thermal conductivity of the selected aluminum-based material and ceramic reinforcement, and will not generate sparks under high-speed braking. It can be applied to some special production fields, such as special vehicles in the fields of mining and smelting, and energy transportation. The dual-phase ceramic particle gradient-enhanced aluminum-based vehicle brake disc of the present invention has a non-continuous distribution of functional structures on its friction braking surface, which is conducive to the release of friction stress and friction heat diffusion between the functional structure and the disc base during braking, thereby improving the life of the brake disc and increasing the reliability of vehicle braking; compared with traditional vehicle brake discs, brake discs with functional structural configurations have higher artistic added value, and the configuration can also be customized according to customer requirements to meet personalized market needs. The dual-phase ceramic particle gradient-enhanced aluminum-based vehicle brake disc of the present invention can be repaired by using a silk-powder synchronous deposition arc additive manufacturing process after its friction surface and functional structure are worn, which can greatly extend the service life of the vehicle brake disc and further reduce product costs.
[0120] The following further describes the vehicle brake disc and its preparation process of the present application with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0121] In the following examples, the average particle size of TiC ceramic particles is 40 μm; the average particle size of B4C ceramic particles is 100 μm; Example 1
[0122] The present application embodiment provides a vehicle brake disc, which is positioned as a small automobile brake disc, and its structure is as follows: Figures 3-4 As shown, it includes: a disc base and a functional structure layer, and the disc base includes:
[0123] A disc body having a central hole;
[0124] A connecting part, which is located in the central hole of the disc body and is provided with a connecting hole;
[0125] The functional structural layers are respectively embedded on two surfaces of the disc body;
[0126] One end surface of each functional structure layer is embedded in the disc body, and the other end surface is flush with the surface of the disc body;
[0127] A cover layer is provided on the surface of the functional structure layer;
[0128] Among them, the outer diameter of the disc body is 250mm and the thickness is 25mm;
[0129] The cross-sectional shape of the functional structure layer is annular, and the functional structure layer is three concentric rings staggered inside and outside. The width of the ring segment is 15 mm, the spacing is 30 mm, the difference in radius between the inner and outer rings is 25 mm, and the thickness of the functional structure layer is 8 mm.
[0130] The functional structure layer includes the first layer, the second layer, the third layer, the fourth layer, the fifth layer, the sixth layer, the seventh layer, and the eighth layer stacked in sequence from the end surface embedded in the disc body to the surface direction of the disc base; wherein the thickness of each layer is 1 mm;
[0131] Layers 1 to 5 are the multiple first sub-functional layers mentioned above (including Al5356 alloy matrix and TiC ceramic particles), and layers 6 to 8 are the multiple second sub-functional layers mentioned above (including Al5356 alloy matrix, TiC ceramic particles and B4C ceramic particles);
[0132] The first layer is Al5356 alloy (the volume fraction of TiC ceramic particles is 0%);
[0133] The second layer includes Al5356 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the second layer is 5%;
[0134] The third layer includes Al5356 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the third layer is 10%;
[0135] The fourth layer includes Al5356 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the fourth layer is 15%;
[0136] The fifth layer includes Al5356 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the fifth layer is 20%;
[0137] The sixth layer includes Al5356 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of TiC ceramic particles in the sixth layer is 15%, and the volume fraction of B4C ceramic particles is 4%.
[0138] The seventh layer includes Al5356 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of TiC ceramic particles in the seventh layer is 10%, and the volume fraction of B4C ceramic particles is 7%.
[0139] The eighth layer includes Al5356 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of the TiC ceramic particles in the eighth layer is 5%, and the volume fraction of the B4C ceramic particles is 10%.
[0140] The end surface of the functional structure layer is flush with the surface of the disc body, and the thickness of the cover layer is 0.5mm;
[0141] The material of the disc base is ZL101, and its composition (mass fraction) is: Si 6.5-7.5%, Mg 0.25-0.45%, Fe<0.5%, Cu<0.2%, Zn<0.3%, Mn<0.35%, and Al balance; the cover layer is Al5356 alloy, and its composition (mass fraction) is: Mg 5.0%, Si 0.25%, Fe 0.4%, Cu 0.1%, Zn 0.1%, Mn 0.12%, Cr 0.13%, Ti0.13%, and Al balance.
[0142] Specifically, refer to Fig.10 As shown, it shows the change pattern of the volume fraction of TiC ceramic particles and B4C ceramic particles in each layer in Example 1.
[0143] The preparation process of the vehicle brake disc in the above-mentioned embodiment 1 comprises the following steps:
[0144] S1. Casting of the brake disc base embryo: Using the traditional pressure casting method, the smelted ZL101 is cast into the prepared brake disc mold at a temperature range of 680-750°C, ensuring that the disc base embryo is 1-2mm larger than the design size of the brake disc by a processing allowance;
[0145] S2. Mechanical processing of the brake disc base. The disc base embryo is machined to the designed size by turning and milling, and a groove with the same design size as the functional structure layer is machined on the surface of the disc base, and a connecting hole is machined;
[0146] S3. According to the structure of the functional structural layer, the digital model of the vehicle brake disc is imported into the additive manufacturing system, the functional structural layer is sliced and the additive manufacturing deposition path is automatically generated;
[0147] S4. Arc additive manufacturing of brake disc functional structure. Fix the machined disc base on the positioner, clean and dry the surface of the disc base; load the dried TiC ceramic particles and B4C ceramic particle powder into independent powder feeders respectively, install the Al5356 alloy welding wire with a diameter of 1.2mm on the automatic wire feeder to ensure smooth wire and powder feeding; start the control program, and the wire-powder composite welding gun performs arc additive deposition under the control of the CNC machine tool or robot; the additive deposition current is 95A, the fuse speed is about 5.0m / min, and the arc swing amplitude is 6m m, the swing frequency is 3Hz, the shielding gas and powder feeding gas are both 99.999% high-purity Ar gas; the capture rate of the molten pool for TiC powder is 70%, and the capture rate for B4C powder is 40%. The powder feeding rate of the ceramic powder can be determined according to the design content of the ceramic particles in the corresponding deposition layer; according to the requirements of the layered design of the functional structure layer, the program chooses to open or close the powder feeding channel of the powder feeder storing the corresponding ceramic powder, and executes the corresponding powder feeding rate: Among them, when depositing the second layer, the powder feeding rate of the TiC ceramic particles is controlled to be 2.10g / min; when depositing the third layer, the powder feeding rate of TiC ceramic particles was controlled to be 4.42 g / min; when depositing the fourth layer, the powder feeding rate of TiC ceramic particles was controlled to be 6.99 g / min; when depositing the fifth layer, the powder feeding rate of TiC ceramic particles was controlled to be 9.95 g / min; when depositing the sixth layer, the powder feeding rate of TiC ceramic particles was controlled to be 7.37 g / min, and the powder feeding rate of B4C ceramic particles was 1.75 g / min; when depositing the seventh layer, the powder feeding rate of TiC ceramic particles was controlled to be 4 .80g / min, the powder feeding rate of B4C ceramic particles is 2.99g / min; when depositing the 8th layer, the powder feeding rate of TiC ceramic particles is controlled to be 2.34g / min, and the powder feeding rate of B4C ceramic particles is 4.17g / min; the protective gas flow rate is 15L / min, the powder feeding gas flow rate is 5L / min, and the B4C powder feeding gas flow rate is 3L / min; finally, the functional structure layer is prepared; at the same time, a capping layer is deposited on the functional structure layer; finally, the capping layer is 1 to 2mm higher than the surface of the disc base;
[0148] S5. Finishing of brake disc. Finishing of the brake disc with functional structure is performed. To avoid damage to the tool by ceramic, the cover layer is ground to a height not higher than 1 mm (specifically 0.5 mm) above the surface of the disc base by a grinding process.
[0149] Example 2
[0150] The present application embodiment provides a vehicle brake disc, which is positioned as a medium-to-large automobile brake disc, and its structure is as follows: Figures 5-6 As shown, it includes: a disc base and a functional structure layer, and the disc base includes:
[0151] A disc body having a central hole;
[0152] A connecting part, which is located in the central hole of the disc body and is provided with a connecting hole;
[0153] The functional structural layers are respectively embedded on two surfaces of the disc body;
[0154] One end surface of each functional structure layer is embedded in the disc body, and the other end surface is flush with the surface of the disc body;
[0155] A cover layer is provided on the surface of the functional structure layer;
[0156] The outer diameter of the disc is 400mm, the thickness is 30mm, and the circumference of the disc is provided with a plurality of ventilation holes;
[0157] The cross-sectional shape of the functional structure layer is an involute shape, the line width of the functional structure layer is 25 mm, the start and end of the functional structure layer are 10 mm away from the inner and outer edges of the brake disc braking surface, and the thickness of the functional structure layer is 10 mm;
[0158] The functional structure layer includes a first layer, a second layer, a third layer, a fourth layer, a fifth layer, a sixth layer, a seventh layer, an eighth layer, a ninth layer, and a tenth layer stacked in sequence from the end surface embedded in the disc body to the surface direction of the disc base; wherein the thickness of each layer is 1 mm;
[0159] Layers 1 to 6 are the multiple first sub-functional layers mentioned above (including Al5356 alloy matrix and TiC ceramic particles), and layers 7 to 10 are the multiple second sub-functional layers mentioned above (including Al5356 alloy matrix, TiC ceramic particles and B4C ceramic particles);
[0160] The first layer is Al5083 alloy (the volume fraction of TiC ceramic particles is 0%);
[0161] The second layer includes Al5083 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the second layer is 5%;
[0162] The third layer includes Al5083 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the third layer is 10%;
[0163] The fourth layer includes Al5083 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the fourth layer is 15%;
[0164] The fifth layer includes Al5083 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the fifth layer is 20%;
[0165] The sixth layer includes Al5083 alloy and TiC ceramic particles, and the volume fraction of TiC ceramic particles in the sixth layer is 23%;
[0166] The seventh layer includes Al5083 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of TiC ceramic particles in the seventh layer is 18%, and the volume fraction of B4C ceramic particles is 3%.
[0167] The eighth layer includes Al5083 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of TiC ceramic particles in the eighth layer is 12%, and the volume fraction of B4C ceramic particles is 7%.
[0168] The ninth layer includes Al5083 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of the TiC ceramic particles in the ninth layer is 8%, and the volume fraction of the B4C ceramic particles is 9%.
[0169] The tenth layer includes Al5083 alloy, TiC ceramic particles, and B4C ceramic particles. The volume fraction of TiC ceramic particles in the tenth layer is 3%, and the volume fraction of B4C ceramic particles is 12%.
[0170] The end surface of the functional structure layer is flush with the surface of the disc body, and the thickness of the cover layer is 0.5mm;
[0171] The material of the disc base is ZL303, and its composition (mass fraction) is: Mg 4.5-5.5%, Si 0.8-1.3%, Mn0.1-0.4%, Fe<0.5%, Cu<0.1%, Zn<0.2%, Ti<0.2%, and Al balance; the cover layer is Al5083 alloy, and its composition (mass fraction) is: Mg 4.5-5.2%, Mn 0.5-1.0%, Cr 0.15-0.25%, Si 0.4%, Fe 0.4%, Cu0.1%, Zn0.25%, Ti 0.15%, and Al balance.
[0172] The preparation process of the vehicle brake disc in the above-mentioned embodiment 2 comprises the following steps:
[0173] S1. Casting of the brake disc base embryo: Using the traditional pressure casting method, the smelted ZL303 is cast into the prepared brake disc mold at a temperature range of 650-720°C, ensuring that the disc base embryo is 1-2mm larger than the design size of the brake disc by a processing allowance;
[0174] S2. Mechanical processing of the brake disc base. The disc base blank is machined to the designed size by turning and milling, and a groove with the same design size as the functional structure layer is machined in the brake area of the disc base, and connection holes and ventilation holes are machined;
[0175] S3. According to the structure of the functional structural layer, the digital model of the vehicle brake disc is imported into the additive manufacturing system, the functional structural layer is sliced and the additive manufacturing deposition path is automatically generated;
[0176] S4. Arc additive manufacturing of brake disc functional structure. Fix the machined disc base on the positioner, clean and dry the disc base surface; load the dried TiC ceramic particles and B4C ceramic particle powder into independent powder feeders respectively, install the Al5083 alloy welding wire with a diameter of 1.2mm on the automatic wire feeder to ensure smooth wire and powder feeding; start the control program, and the wire-powder composite welding gun performs arc additive deposition under the control of the CNC machine tool or robot; the additive deposition current is 105A, the fuse speed is about 5.2m / min, the arc swing amplitude is 8mm, the arc swing frequency is 2Hz, and the shielding gas and powder feeding gas are both 99 .999% high-purity Ar gas; the capture rate of the molten pool for TiC powder is 70%, and the capture rate for B4C powder is 40%. The powder feeding rate of the ceramic powder can be determined according to the designed content of ceramic particles in the corresponding deposition layer; according to the requirements of the layered design of the functional structure layer, the program chooses to open or close the powder feeding channel of the powder feeder storing the corresponding ceramic powder, and executes the corresponding powder feeding rate: when depositing the second layer, the powder feeding rate of the TiC ceramic particles is controlled to be 2.18g / min; when depositing the third layer, the powder feeding rate of the TiC ceramic particles is controlled to be 4.60g / min; when depositing the fourth layer, the T The powder feeding rate of iC ceramic particles is 7.31g / min; when depositing the 5th layer, the powder feeding rate of TiC ceramic particles is controlled to be 10.35g / min; when depositing the 6th layer, the powder feeding rate of TiC ceramic particles is controlled to be 12.37g / min; when depositing the 7th layer, the powder feeding rate of TiC ceramic particles is controlled to be 9.43g / min, and the powder feeding rate of B4C ceramic particles is 1.40g / min; when depositing the 8th layer, the powder feeding rate of TiC ceramic particles is controlled to be 6.13g / min, and the powder feeding rate of B4C ceramic particles is 3.19g / min; When depositing the 9th layer, the powder feeding rate of TiC ceramic particles is controlled to be 3.99g / min, and the powder feeding rate of B4C ceramic particles is controlled to be 3.40g / min; when depositing the 10th layer, the powder feeding rate of TiC ceramic particles is controlled to be 1.46g / min, and the powder feeding rate of B4C ceramic particles is controlled to be 5.21g / min; the protective gas flow rate is 15L / min, the powder feeding gas flow rate is 5L / min, and the B4C powder feeding gas flow rate is 3L / min; finally, the functional structure layer is prepared; at the same time, the capping layer is deposited on the functional structure layer; finally, the capping layer is 1 to 2mm higher than the surface of the disc base;
[0177] S5. Finishing of brake disc. Finishing of the brake disc with functional structure is performed. To avoid damage to the tool by ceramic, the cover layer is ground to a height not higher than 1 mm (specifically 0.5 mm) above the surface of the disc base by a grinding process.
[0178] Example 3
[0179] The vehicle brake disc provided in this embodiment is the same as that in Embodiment 1, except that the material of the disc base is A356, and its composition (mass fraction) is: Si 6.5-7.5%, Mg 0.25-0.45%, Fe<0.2%, Cu<0.1%, Zn<0.1%, Mn<0.1%, Ti<0.2%, Al balance, and the rest is the same as that in Embodiment 1;
[0180] The preparation process of the vehicle brake disc provided in Example 3 is the same as that in Example 1, except that step S1 is: using the traditional pressure casting method, the melted A356 is cast into the prepared brake disc mold within the temperature range of 660 to 720°C, ensuring that the disc base embryo has a processing allowance of 1 to 2 mm larger than the design size of the brake disc; the rest of the processes are the same as in Example 1.
[0181] Example 4
[0182] The vehicle brake disc provided in this embodiment is the same as that in Embodiment 1, except that Figures 7-8 As shown, the cross-sectional shape of the functional structure layer is an elliptical ring, and two elliptical ring-shaped functional structure layers of different sizes are staggered inside and outside, the major axis of the large elliptical ring-shaped functional structure layer is 36mm, the minor axis is 15mm, and the ring width is 12mm, the major axis of the small elliptical ring-shaped functional structure layer is 16mm, the minor axis is 10mm, the ring width is 6mm, and the thickness of the functional structure layer is 8mm; the rest is the same as Example 1;
[0183] The preparation process of the vehicle brake disc provided in Example 4 is the same as that in Example 1, except that the additive deposition paths of the functional structural layers of different shapes and sizes are different.
[0184] Example 5
[0185] The vehicle brake disc provided in this embodiment is the same as that in Embodiment 2, except that Figures 9-10 As shown, the cross-sectional shape of the functional structural layer is a rhombus-shaped sheet, and two rhombus-shaped functional structural layers of different sizes are alternately staggered inside and outside, the side length of the large rhombus-shaped functional structural layer is 40 mm, the obtuse angle is 125°, the sheet length of the small rhombus-shaped functional structural layer 2 is 35 mm, and the obtuse angle is 100°; the thickness of the functional structural layer is 10 mm; the rest is the same as Example 2;
[0186] The preparation process of the vehicle brake disc provided in Example 5 is the same as that in Example 2, except that the additive deposition paths of the functional structural layers of different shapes and sizes are different.
[0187] Comparative Example 1
[0188] This comparative example provides a conventional vehicle brake disc without a functional structural layer, specifically comprising: a disc base;
[0189] The disc base comprises: a disc body having a central hole;
[0190] A connecting part, which is located in the central hole of the disc body and is provided with a connecting hole;
[0191] The outer diameter of the disc is 250mm, the thickness is 30mm, and the circumference of the disc is provided with a plurality of ventilation holes;
[0192] The material of the disc base is HT250, and its composition (mass fraction) is: C 3.96%, Si 1.44%, Mn 0.65%, Cu 0.37%, Sn 0.04%, K 0.05%, B 0.004%, Ce 0.003%, Al 0.25%, Ca 0.04%, S 0.029%, P 0.059%, and the balance Fe.
[0193] Performance Testing
[0194] The performance of the vehicle brake discs in Examples 1 to 5 and Comparative Example 1 was tested, and the results are shown in Table 1 below.
[0195] Table 1 - Performance of vehicle brake discs in Examples 1 to 5 and Comparative Example 1
[0196]
[0197] It can be seen from Table 1 that the thermal conductivity of the vehicle brake disc in Examples 1 to 5 is 150 to 190 W / m·K, and the damping coefficient is (0.8 to 1.2)×10 -2, the friction coefficient is 0.4-0.6; the TiC and B4C dual-phase ceramic particles of the present invention selectively gradient reinforced aluminum-based vehicle brake disc, the tensile strength of the disc base and the lower half of the functional structure layer is 250-280MPa, and the elongation is 10-15%, which are higher than the 240-250MPa and 0.5-1.0% of the traditional gray cast iron (HT250) brake disc in Comparative Example 1; the strength of the upper half of the functional structure layer is equivalent to that of the HT250 brake disc in Comparative Example 1, the thermal conductivity is more than 3 times that of the HT250 brake disc in Comparative Example 1, the shock absorption (damping) is better than that of the HT250 brake disc in Comparative Example 1, the friction coefficient and braking capacity are equivalent to those of the HT250 brake disc in Comparative Example 1, the volume wear per unit time is 1 / 3-1 / 5 of that of the HT250 brake disc in Comparative Example 1, and the wear resistance far exceeds that of the HT250 brake disc.
[0198] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A vehicle brake disc, characterized in that: include: Disc base; Functional structural layers are respectively embedded on two surfaces of the disc base; Wherein, one end surface of each of the functional structural layers is embedded in the disc base, and the other end surface is flush with the surface of the disc base; The functional structural layer includes a matrix, TiC ceramic particles, and B4C ceramic particles; Wherein, the volume fraction of the TiC ceramic particles increases with the increase of the thickness of the functional structure layer from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer; When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of its thickness, the volume fraction of the TiC ceramic particles decreases as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles increases as the thickness of the functional structure layer increases.
2. The vehicle brake disc according to claim 1, characterized in that The functional structure layer is from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer, the volume fraction of the TiC ceramic particles increases from 0% to 20 to 30% as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles is 0%; When the thickness of the functional structure layer exceeds 1 / 2 to 5 / 8 of the thickness of the functional structure layer, the volume fraction of the TiC ceramic particles decreases from 20 to 30% to 3 to 5% as the thickness of the functional structure layer increases, and the volume fraction of the B4C ceramic particles increases from 0% to 10 to 20% as the thickness of the functional structure layer increases.
3. The vehicle brake disc according to claim 2, characterized in that The functional structure layer extends from the end surface embedded in the disc base to the position of 1 / 2 to 5 / 8 of the thickness of the functional structure layer, and the functional structure layer includes a plurality of first sub-functional structure layers stacked in layers, and the volume fraction of B4C ceramic particles in each first sub-functional structure layer is 0%; wherein the volume fraction of TiC ceramic particles in the first sub-functional structure layer farthest from the surface of the disc base is 0%, and the volume fraction difference of TiC ceramic particles in any two adjacent first sub-functional structure layers is 3 to 5%; The thickness of the functional structure layer is from 1 / 2 to 5 / 8 of the thickness of the functional structure layer to the end face flush with the surface of the disc base, and the functional structure layer includes a plurality of stacked second sub-functional structure layers; wherein the volume fraction of TiC ceramic particles in the second sub-functional structure layer farthest from the surface of the disc base is 15 to 25%, the volume fraction of B4C ceramic particles is 3 to 4%, the volume fraction difference of TiC ceramic particles in any two adjacent second sub-functional structure layers is 4 to 6%, and the volume fraction difference of B4C ceramic particles is 2 to 4%.
4. The vehicle brake disc according to claim 1, characterized in that The particle size of the TiC ceramic particles is 25 to 60 μm; the particle size of the B4C ceramic particles is 45 to 300 μm.
5. The vehicle brake disc according to any one of claims 1 to 4, characterized in that: The disc base comprises: A disc body having a central hole; A connecting portion, which is located in the central hole of the disc body, and is provided with a connecting hole; The functional structural layers are respectively embedded on two surfaces of the disc body; One end surface of each functional structure layer is embedded in the disc body, and the other end surface is flush with the surface of the disc body.
6. The vehicle brake disc according to claim 5, characterized in that The cross-sectional shape of the functional structural layer is any one of a circular ring shape, an involute shape, an elliptical ring shape, and a diamond sheet shape.
7. The vehicle brake disc according to any one of claims 1 to 4, characterized in that: The end surface of the functional structure layer that is flush with the surface of the disc base is also provided with a capping layer; The material of the disc base includes any one of Al-Si alloy and Al-Mg alloy; The material of the substrate is Al-Mg alloy; The material of the capping layer is Al-Mg alloy; The thickness of the functional structure layer is 30-35% of the thickness of the disc base; The distance between the end surface of the cover layer away from the disc base and the surface of the disc base is less than or equal to 1 mm.
8. A process for preparing a vehicle brake disc as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: preparing a disc base; Grooves are respectively machined on two surfaces of the disc base, and the grooves are adapted to the functional structure layer; Determining an additive manufacturing deposition path according to the structure of the functional structural layer; TiC ceramic particles and B4C ceramic particles are placed in two powder feeders with independent powder feeding channels respectively, and the two powder feeding channels are connected to a wire-powder synchronous deposition composite welding gun head; Install the alloy welding wire corresponding to the substrate on the wire feeder; According to the additive manufacturing deposition path, arc additive deposition is carried out and the powder feeding rate of TiC ceramic particles and B4C ceramic particles is controlled to print the functional structure layer in the groove.
9. The process for preparing a vehicle brake disc according to claim 8, characterized in that: The process parameters controlled during arc additive deposition are: deposition current of 90-110A, fuse speed of 5.0-6.0m / min, arc swing amplitude of 4-10mm, arc swing frequency of 2-5Hz, capture rate of TiC ceramic particles by the molten pool of 60-70%, and capture rate of B4C ceramic particles by the molten pool of 30-40%.
10. The process for preparing a vehicle brake disc according to claim 8, characterized in that: The disc base is prepared by pressure casting process; After the functional structure layer is prepared, a cap layer is prepared on the surface of the functional structure layer, and then the cap layer is ground so that the distance between the end surface of the cap layer and the surface of the disc base is less than or equal to 1 mm; During arc additive deposition, the width of a single deposition layer is 5 to 20 mm, and the thickness of each layer is 0.5 to 2 mm.
Citation Information
Patent Citations
Aluminum-based composite brake disc and manufacturing method
CN106812837A
Aluminum-based composite material vehicle brake disc preparation method
CN107760894A
Dual-phase ceramic particle reinforced aluminum-based composite material and drum brake and preparation method thereof
CN111074109A